Pengaruh Edukasi Booklet terhadap Kepatuhan Minum Obat pada Pasien Hipertensi Peserta Prolanis di Puskesmas Butang Baru Kabupaten Sarolangun - Sari, Trisia Mayang; Sari, Yelly Oktavia; Wahyuni, Fatma Sri (Journal of Pharmaceutical and Sciences, 2025)
Background: Hypertension is a global health problem with a high prevalence and is a significant risk factor for cardiovascular disease. Low medication adherence remains a challenge in the long-term management of hypertension. Health education is a key strategy to improve patients’ understanding and adherence. Booklets are considered a potential educational medium for delivering information in a structured manner. Objective: This study aims to analyse the effect of booklet media education on medication adherence among hypertensive patients participating in the Prolanis program at Butang Baru Public Health Centre, Sarolangun Regency. Methods: This research employed a pretest-posttest control group experimental design. Fifty-six respondents were evenly divided into the intervention group (received booklet-based education) and the control group (received no intervention). Medication adherence was measured using the MARS-5 questionnaire. Data were analysed using the Wilcoxon Signed Ranks test. Results: There was a significant improvement in adherence in the intervention group. The percentage of patients with high adherence increased from 7.14% to 53.57%, while the low adherence category decreased from 25% to 0%. Conversely, the control group showed no meaningful changes. Statistical analysis confirmed these findings, with a p-value = 0.000 (p < 0.05), indicating that the booklet intervention significantly improved adherence. Conclusion: Education through booklet media was proven effective in improving medication adherence among hypertensive patients. Therefore, booklets can be applied as a practical and beneficial intervention strategy to support the success of chronic disease management programs such as Prolanis in primary health care settings.